Harnessing green manuring for nature-based sustainable soil management in Bangladesh - Ahmed, Sharif; Miajy, Abdullah; Debnath, Manik; Bhandari, Humnath (International Rice Research Institute, 2025)
Do we know that most agricultural soils in Bangladesh are low in organic matter, with levels less than 1–2%, which is significantly below the ideal range of 3–5% required for soil fertility? The main reasons for low soil fertility in Bangladeshi soils include continuous cropping without adequate nutrient replenishment, overuse of chemical fertilizers, less crop diversification, complete crop residue removal practices, and inadequate organic matter additions. Soil fertility is the cornerstone of productive agriculture, yet modern farming practices increasingly threaten its health. Agriculture is the backbone of the Bangladesh economy, and here, sustainable crop production largely depends on soil health conditions. Organic matter is considered the life of soil because it serves as a reservoir of microorganisms and source of nutrients such as nitrogen, phosphorus, sulfur, and micronutrients. The beneficiary microorganisms of soil, which can help decompose plant foods from inorganic and organic sources, can’t survive in soil without organic matter. Moreover, organic matter acts as a binding agent, promoting the formation of stable soil aggregates and improving porosity, aeration, and root penetration. It also increases the soil’s cation exchange capacity, helping nutrients remain available rather than leach away. In addition to soil fertility and physical improvement, organic matter helps in the sequestration of carbon in soil to mitigate greenhouse gas emissions.